NILAI-NILAI ISLAM DALAM SUDUT PANDANG PRAKTIK MANAJAMEN PENDIDIKAN BERBASIS ISLAM - Taufiqur Rohamn, Wahyu; Asari, Asari; Iskarim, Mochamad (Pimpinan Cabang Muhammadiyah Kramat Jati, 2024)
Islamic education management is the process of utilizing resources to achieve predetermined goals efficiently, effectively and productively, while Islamic education is an educational concept based on Islamic values ​​to form knowledgeable and skilled Muslim individuals. The aim of Islamic education management is that all things and processes that take place can be truly managed well so that the educational process can truly be realized in accordance with Islamic teachings and. Efforts to achieve the goals of Islamic education can be more easily realized. The scope of practice of Islamic education management includes institutional management and Islamic education programs as well as aspects of the Islamic spirit inherent in every educational activity.